Preservation Concepts in Secondary Rhinoplasty: Is There Any Role? - Robotti, Enrico; Ilambarathi, Gowthaman; Cottone, Giuseppe; Leone, Francesco; Robotti, Sara; Alessandri Bonetti, Mario (Facial Plastic Surgery, 2025)
Secondary rhinoplasty presents complex challenges due to anatomical distortions, scar tissue, and multiple iatrogenic deformities.Although a traditional structural approach is the time-honored benchmark against which any other technique should be measured, preservation concepts can be integrated together with structural techniques.This study is based on a retrospective review of cases.Preservation concepts applicable to secondary rhinoplasty are outlined in detail. A paradigm case highlighting the strategic application of preservation techniques is included.Preservation concepts pose an evident advantage in avoiding unnecessary dissection, further destabilization, and overgrafting while maintaining native structures that can be preserved and limiting dead space. Scar tissue can be used advantageously rather than discarded. However, introducing a “preservationist mindset” in revision rhinoplasty needs a refined approach, mastery of diverse techniques, and a flexible operative strategy.Preservation concepts can lead to improved outcomes even in secondary rhinoplasty.
Keywords: rhinoplasty; septoplasty; preservation; secondary; revision